Amazonian tuber starch based films incorporated with silver nanoparticles for preservation of fruits (Research, Society and Development, 2021)
Films and coatings based on natural polymers are used to conserve nutritional quality of fruits, vegetables and also delay their ripening. The purpose of this study was to develop films with starch extracted from Dioscorea altissima Lam. (dunguey) incorporated with silver nanoparticles for coating and preserving fruits. The films obtained by cast were characterized visually, by Scanning Electron Microscope, by Atomic Force Microscopy, by X-Ray Diffraction and by Fourier-Transform Infrared Spectroscopy. Antimicrobial activity and technological properties were also evaluated. The coating of camu-camu fruits [Myrciaria dubia (Kunth) McVaugh] was carried out by immersing them in the filmogenic solution, followed by their physicochemical and microbiological analysis. The films with silver nanoparticles showed transparency, flexibility, spherical clusters and a higher average roughness. A reduction in thickness, solubility and water vapor permeability was also observed. Antimicrobial action against Staphylococcus aureus and Escherichia coli was proved as well. The fruits coated with films exhibited delay in ripening, with maintenance of quality and longevity. Uncoated fruits showed greater wilting and wrinkling. The starch film incorporated with silver nanoparticles was effective for preserving camu-camu fruit.